Electrode-stress-induced nanoscale disorder in Si quantum electronic devices - J. Park; Y. Ahn; J. A. Tilka; K. C. Sampson; D. E. Savage; J. R. Prance; C. B. Simmons; M. G. Lagally; S. N. Coppersmith; M. A. Eriksson; M. V. Holt; P. G. Evans (APL Materials, 2016)
Disorder in the potential-energy landscape presents a major obstacle to the more rapid development of semiconductor quantum device technologies. We report a large-magnitude source of disorder, beyond commonly considered unintentional background doping or fixed charge in oxide layers: nanoscale strain fields induced by residual stresses in nanopatterned metal gates. Quantitative analysis of synchrotron coherent hard x-ray nanobeam diffraction patterns reveals gate-induced curvature and strains up to 0.03% in a buried Si quantum well within a Si/SiGe heterostructure. Electrode stress presents both challenges to the design of devices and opportunities associated with the lateral manipulation of electronic energy levels.